Financial Constraints to Entrepreneurial in Sudan: An Applied Analytical Study - Elneel, Faiez Ahmed Mohamed Hamed (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to measure the impact of the financing obstacles related to entrepreneurs on the financing obstacles related to financing institutions, and vice versa, to achieve policy recommendations that help in overcoming those obstacles that face the financing of entrepreneurial in Sudan. The study followed the descriptive and analytical approach using the multiple linear regression and A nova analysis method to estimate the study models and test the hypotheses. The study relied on primary data from a questionnaire distributed to (54) employees of entrepreneurship financing institutions in Sudan. The study recommends the necessity of restructuring and empowering institutions were working in entrepreneurship and microfinance so that to finance the operations directly by enacting new laws and legislations, reviewing existing legislation and laws, and finding a new financing formula for entrepreneurship that is compatible with the culture and legacies of Sudanese community through reviewing the legislative and legal frameworks. A coordination between entrepreneurial projects, microfinance institutions and banks, and other relevant one, also recommended. In addition to providing a database and adequate information on entrepreneurship, providing the necessary guidance and training before yielding finance and raising the level of administrative experience and awareness.